TERAPI MASSAGE PADA IBU HAMIL UNTUK MEMBERIKAN RASA NYAMAN DI WILAYAH KERJA PUSKESMAS TANAH KALI KEDINDING SURABAYA - Rachmawati Ika Sukarsih; Nova Elok Mardliyana; Nur Hidayatul Ainiyah; Irma Maya Puspita (STAI Darul Qalam Tangerang, 2021)
A pregnant woman needs special attention and needs a sense of security and comfort with the people around her. In undergoing the process of pregnancy, childbirth and caring for a newborn, a mother must be in a calm and pleasant condition. Physical, psychological and hormonal changes will be experienced during the pregnancy process. Massage therapy is one of the non-pharmacological therapy options that can be applied to pregnant women to increase comfort for pregnant women. This community service activity is applied to pregnant women who live in the Tanah Kali Kewall Health Center area of ​​Surabaya City. This activity uses the practical method of doing massage for pregnant women with homecare. Implementation time during February 2020. The target is pregnant women with a gestational age of 20-35 weeks as many as 11 people. This activity has an impact on the community, especially pregnant women who feel more comfortable after being given massage therapy for approximately 60 minutes. This is evidenced by the reduced physical complaints that are felt today and the increased quality of sleep of pregnant women